DEVELOPMENT STRATEGY FOR MARINE TOURISM AT KOMBI BEACH IN NORTH SULAWESI : Strategi Pengembangan Wisata Bahari Pantai Kombi di Sulawesi Utara - Pingkan Aprilia Maramis; Kristi Karla Arina; Priskila Gissela Marlia Walangitan; Sammy Rommy Novie Korua; Jefta Eoudio Jeremia Maramis; Jibrael Albert Jesson Bolung; Gloria Virginia Regita Wangkay (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Marine tourism is an important contributor to the global economy that relies heavily on the preservation of coastal resources (Gössling, Hall, and Scott 2018). Kombi Beach, which is located in Kombi District, is not only known by local tourists, but also begins to attract the attention of foreign tourists. However, the development of marine tourism on Kombi Beach still faces various challenges, including limited infrastructure, suboptimal promotion, and public awareness of the importance of sustainable tourism. However, despite having various advantages, Kombi Beach still faces a number of challenges that need to be overcome in order to compete with other tourist destinations around it. The data analysis in this study uses SWOT analysis. Based on the results of the SWOT analysis for the marine tourism development strategy on Kombi Beach, which resulted in several important points. First, the strength of Kombi Beach lies in its unique natural beauty, climate that supports tourism throughout the year, as well as support from the government and local communities. Second, the weaknesses faced include limited supporting infrastructure, less than optimal promotion, and the quality of human resources in the tourism sector that need to be improved. Furthermore, the opportunities that exist include increasing marine tourism trends, potential investment from the private sector, and advances in digital technology that can increase promotion. However, the challenges that must be watched out for are competition with other tourist destinations, potential environmental damage, and economic instability that can affect tourist visits. Based on the analysis, the recommended development strategy is an aggressiveness (SO) strategy. Steps that can be taken include the development of integrated tour packages that combine natural and cultural activities, utilizing digital promotion with government support, involving local communities in tourism efforts, and collaborating with the government to improve transportation access